2021
DOI: 10.1002/adma.202106265
|View full text |Cite
|
Sign up to set email alerts
|

Mesenchymal Stem Cell‐Derived Extracellular Vesicles with High PD‐L1 Expression for Autoimmune Diseases Treatment

Abstract: Autoimmune diseases are the third most common disease influencing the quality of life of many patients. Here, a programmed cell death‐ligand 1 + (PD‐L1) mesenchymal stem cell (MSC) derived extracellular vesicles (MSC‐sEVs‐PD‐L1) using lentivirus‐mediated gene transfection technology is developed for reconfiguration of the local immune microenvironment of affected tissue in autoimmune diseases. MSC‐sEVs‐PD‐L1 exhibits an impressive ability to regulate various activated immune cells to an immunosuppressed state … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(91 citation statements)
references
References 50 publications
1
90
0
Order By: Relevance
“…Since the application value of MSCs lies in clinical treatment, the safety of the method is particularly important when developing improved technologies. Several studies have been published in which MSCs have been genetically modified based on viral transfection techniques (38)(39)(40). Although these methods can directly transform MSCs, the off-target effects associated with genetic modification and the safety of residual vectors such as viruses still pose a major obstacle to clinical transformation.…”
Section: Discussionmentioning
confidence: 99%
“…Since the application value of MSCs lies in clinical treatment, the safety of the method is particularly important when developing improved technologies. Several studies have been published in which MSCs have been genetically modified based on viral transfection techniques (38)(39)(40). Although these methods can directly transform MSCs, the off-target effects associated with genetic modification and the safety of residual vectors such as viruses still pose a major obstacle to clinical transformation.…”
Section: Discussionmentioning
confidence: 99%
“…The regulation of immune checkpoint pathway plays pivotal roles in the treatment of immune system diseases ( 85 ). Among them, the programmed cell death-1 (PD-1)/programmed cell death-ligand 1 (PD-L1) checkpoint pathway is one of the important components to inhibit the immune response and maintain immune homeostasis ( 86 ). PD-1, a costimulatory molecule, is induced to be expressed on the surface of activated T cells, B cells and NK cells.…”
Section: Mechanisms Of Mscs-based Therapy Of Ibdsmentioning
confidence: 99%
“…Chen et al earlier investigated the therapeutic effect of bone marrow MSCs (BM-MSCs) transplantation in experimental autoimmune hepatitis (EAH) in mice and showed that BMSCs transplantation, especially multi-dose transplantation, increased hepatic PD-L1 levels along with decreased IL-17 levels, producing immunosuppressive effects [ 436 ]. Similarly, a recent study used lentiviral transfection to construct PD-L1-high expressing MSCs-EVs, which successfully initiated immunosuppressive signaling in activated immune cells, including T cells, macrophages and DCs, by interacting with PD-1 on the surface of these cells [ 437 ]. By constructing mouse autoimmune disease models of ulcerative colitis and psoriasis, this study further revealed that extracellular vesicles with high PD-L1 expression could specifically target liver lesion sites and effectively modulate the balance between Th1, Th2, Th17 and Treg cells subsets to attenuate autoimmune responses in AIH [ 437 ].…”
Section: Mscs For Inflammatory Liver Diseasesmentioning
confidence: 99%
“…Similarly, a recent study used lentiviral transfection to construct PD-L1-high expressing MSCs-EVs, which successfully initiated immunosuppressive signaling in activated immune cells, including T cells, macrophages and DCs, by interacting with PD-1 on the surface of these cells [ 437 ]. By constructing mouse autoimmune disease models of ulcerative colitis and psoriasis, this study further revealed that extracellular vesicles with high PD-L1 expression could specifically target liver lesion sites and effectively modulate the balance between Th1, Th2, Th17 and Treg cells subsets to attenuate autoimmune responses in AIH [ 437 ].…”
Section: Mscs For Inflammatory Liver Diseasesmentioning
confidence: 99%